Correlation between the electric and acoustic signals emitted during compression of brittle materials (Fracture and Structural Integrity, 2017)
An experimental protocol is described including a series of uniaxial compression tests of three brittle materials (marble, mortar and glass). The Acoustic Emission (AE) technique and the Pressure Stimulated Currents (PSC) one are used since the recordings of both techniques are strongly related to the formation of cracking in brittle materials. In the present paper, the correlation of these techniques is investigated, which is finally proven to be very satisfactory.
Keywords: Pressure stimulated currents (PSC); Acoustic emission (AE); Compression; Brittle materials